Sport volunteering motivations : gender differences among undergraduates in a sport-related faculty - Chew, Swee Seng. (2013)
With the growth of Singapore's sport industry, more manpower is needed to meet the demands of increasing sporting events. Given the economic and non-economic benefits that young volunteers bring, sport companies and sport event organisers should aim attract more of such personnel. In order to do so, they should have an understanding of sport volunteering motivations and how these motivations differ between genders. This would allow them to customise their recruitment campaigns to target each gender more effectively. The aim of the study was to examine gender differences in sport volunteering motivations. The study used the Volunteer Functions Inventory (VFI) scale to test for importance placed on six motivators (i.e., values, understanding, social, career-related, enhancement, and protective) with regards to sport volunteering. Online questionnaire was sent to undergraduates in a sport-related field of study. There were 126 responses, comprising of 68 males and 58 females. One-way MANOVA testing showed that females placed significantly more importance on values motivator; F(1, 124) = 4.91, p = .028, understanding motivator; F(1, 124) = 5.06, p = .026, and protective motivator; F(1, 124) = 4.43, p = .037. Results implied that volunteer recruitment messages should emphasise on benefits related to values and understanding, especially if the aim is to attract females volunteers, given that these two motivators were also ranked as most important among the six motivators. Ways to improve males' perception towards volunteering should also be looked at by volunteering organisations and government agencies.